Moral puzzles and legal perplexities : essays on the influence of Larry Alexander / edited by Heidi M. Hurd, University of Illinois. - Hurd, Heidi M. (Heidi Margaret), 1960- (Cambridge University Press, 2019)
Drawing inspiration from the profoundly influential work of legal theorist Larry Alexander, this volume tackles central questions in criminal law, constitutional law, jurisprudence, and moral philosophy. What are the legitimate conditions of blame and punishment? What values are at the heart of constitutional protections against discrimination or infringements of free speech? Must judges interpret statutes and constitutional provisions in ways that comport with the intentions of those who wrote them? Can the law obligate us to violate the demands of morality, and when can the law allow the rights of the few to be violated for the good of the many? This collection of essays by world-renowned legal theorists is for anyone interested in foundational questions about the law's authority, the conditions of its fair application to citizens, and the moral justifications of the rights, duties, and permissions that it protects.